Improving the Performance of Wi-Fi Networks by Using the Hysteresis Margin to Reduce Ping-Pong Phenomenon - داؤد ربى; جمال خليفة; مهند عيسى (Latakia University Journal -Engineering Sciences Series, 2024)
The intensive use of wireless devices and the increasing need to support users wherever they are have prompted the search for solutions to enhance the capacity of local wireless networks to support seamless transitions between access points. This study presents a mathematical model for the handover process in wireless networks, specifically within WiFi networks. This model does not rely on a fixed and predetermined signal strength threshold (RSSI_Threshold) to initiate the handover process. Instead, the decision to trigger handover depends on the chosen station’s signal strength surpassing the current station’s signal strength by a margin known as the ’Hysteresis Margin’. This is designed to reduce frequent handovers and the ping-pong effect, particularly in the overlapping coverage area of the current and targeted access points, which adversely affects the continuity and quality of network connectivity. The model was implemented programmatically using Python to simulate and compare the handover process, and the results showed a reduction in the number of handovers when using the hysteresis margin method compared to the traditional method based on a fixed threshold. Furthermore, the study examined the impact of the hysteresis margin value and the distance between connection points on the reduction ratio, enabling the determination of the most suitable values according to the nature of the network.